Effect of Temperature on Flavor Compounds and Sensory Characteristics of Maillard Reaction Products Derived from Mushroom Hydrolysate - Xiao Chen (Molecules, 2018)
Maillard reaction products (MRPs) were prepared from mushroom hydrolysate (MH) by heating with d-xylose and l-cysteine at various temperatures (100 °C–140 °C) for 2 h at a pH of 7.4. The sensory characteristics of MH and MRPs were evaluated by panelists and volatile compounds were analyzed by GC/MS. Additionally, partial least squares regression (PLSR) was performed to analyze the correlation between quantitative sensory characteristics and GC/MS data. GC/MS results revealed that higher reaction temperature resulted in more nitrogen and sulfur containing compounds in MRPs while alcohols, ketones and aldehydes were the major flavor compounds obtained in MH. PLSR results showed that 3-phenylfuran and 2-octylfuran were the compounds responsible for the caramel-like flavor; 1-octen-3-ol, (E)-2-octen-1-ol and geranyl acetone were significantly and positively correlated to mushroom-like flavor, whereas, 2-thiophene-carboxaldehyde, 2,5-thiophenedicarboxaldehyde and 3-methylbutanal positively affected MRPs meat-like attribute. Overall, 125 °C was identified as the optimal temperature for preparing MRPs with abundant volatile compounds and favorable sensory characteristics; the concentration of free amino acids and 5′-GMP, which are associated with the umami taste, in MRPs derived under 125 °C were 3 to 4 times higher than those in MH.